Slow ride - Foster, Lori, 1958- (Foster, Lori, 1958- Road to love series, 2019)
Ronnie Ashford needs a distraction. In the morning, she has to offer arrogant, conventional Jack Crews a job and convince him not to take it. She doesn<U+2019>t need anyone<U+2019>s help, thank you very much. But tonight is all about the tall, sexy stranger who just walked in the bar<U+2014>and all the delicious trouble they could get into together. Too bad just as things are heating up between them, he whispers the three little words that destroy everything: “I<U+2019>m Jack Crews.” Jack is determined to connect with fiery Ronnie<U+2014>in bed and out of it<U+2014>but her terms are clear. If he takes the job, helping her acquire prized artifacts for her mysterious bosses, anything between them is strictly off-limits. Somehow he has to convince a woman who<U+2019>s never felt like she belonged that she<U+2019>s found her place<U+2014>with him. And with the danger sparking hotter than the fire between them, it<U+2019>s going to be one unforgettable trip<U+2026>